Empowering Syrian Women "NGos in city of Lattakia as a model " - عيروط داليا; إيفا خرما (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Syrian society is facing many challenges in the midst of the fierce war it has been exposed to,Especially the Syrian Women, that was the subject of our research, By identing Ngos and their role in empowering women socially and economically, in addition to revealing the most prominent difficulties that women face during their empowerment, it also highlighted needs to achieve social, economic and health empowerment for them, where the course of interviews was adopted with a sample of beneficiaries in tah mosaic society in lattakiam after which some results were reached. One of the most important was the economic empowerment of women through training them in some professions in the association it also empowers them socially by training them in correct social upbringing methods and educating them on some social issues such as early marriage, difficulties in movement and access to the association occupied the first place on the iadder of difficulties facing women to benefit from the services of the association, followed by the local communitys lack of knowledge of the associations activities sometimes.